2010
DOI: 10.1097/01.naj.0000370157.33223.6d
|View full text |Cite
|
Sign up to set email alerts
|

Culture's Effects on Pain Assessment and Management

Abstract: Minority patients are at high risk for poor pain outcomes. When patients belong to a culture or speak a language that's different from that of their health care provider, the provider faces additional challenges in successfully assessing and managing the patients' pain. This article describes how and why culture affects both patients and nurses. It also discusses why members of cultural minority groups frequently receive suboptimal pain management and how nurses can improve patients' pain outcomes by using cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
117
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(124 citation statements)
references
References 36 publications
3
117
0
4
Order By: Relevance
“…In a review of the literature on affective responses to pain Davidhizar and Giger (2004) suggest that diverse cultural responses to pain usually fall into two categories: emotive or stoical, where Amish communities were shown to be stoical, as were the Irish, while Jewish and Italian communities were found to be more emotive. Narayan (2010) reiterates common beliefs that are interpreted as stoical, such as being a 'good patient' means not complaining about pain. There are also certain cultural groups and subcultures in which the notion of stoicism in the face of pain is valued.…”
Section: Culture and Geographies Of Stoicismmentioning
confidence: 99%
“…In a review of the literature on affective responses to pain Davidhizar and Giger (2004) suggest that diverse cultural responses to pain usually fall into two categories: emotive or stoical, where Amish communities were shown to be stoical, as were the Irish, while Jewish and Italian communities were found to be more emotive. Narayan (2010) reiterates common beliefs that are interpreted as stoical, such as being a 'good patient' means not complaining about pain. There are also certain cultural groups and subcultures in which the notion of stoicism in the face of pain is valued.…”
Section: Culture and Geographies Of Stoicismmentioning
confidence: 99%
“…Nurses' ability to identify and adequately manage pain is multifactorial and includes 1) ability to interpret verbal and non-verbal signs of pain, 2) cultural bias 3) knowledge gap and 4) excessive concern about administering pain killers (Sloman,et al , 2001). Narayan (2010) conducted a study and found that registered nurses under-assessed severe pain. The author also revealed that participants had inadequate knowledge about pain, use of analgesics, addiction, and the risks of respiratory depression.…”
Section: Introductionmentioning
confidence: 99%
“…There have been a number of factors highlighted, in the hospital setting, which contribute to the inadequate provision of analgesia. Factors include ED overcrowding (Richardson et al, 2009;Cameron, 2006;Kelen et al, 2001), an increase in patient acuity level (Forero et al, 2008), age (Hwang et al, 2006;Arendts and Fry, 2006), staff and patient beliefs (Finley et al, 2009;Narayan, 2010), as well as inadequate training and competency levels of emergency staff (Ducharme et al, 2008).…”
Section: Introductionmentioning
confidence: 99%